AB0921 Microrna in synovial fluid of ankylosing spondylitis compared with rheumatoid arthritis. (23rd January 2014) - Joo, Y.B.; Kim, J.-J.; Kwon, E.; Lee, B.N.R.; Ji, J.D.; Sung, S.I.; Kim, Y.B.; Kim, T.-H.
Abstract : Background: MicroRNAs have shown different expression patterns in immune disease such as rheumatoid arthritis and systemic lupus erythematosus. However, expression alterations and roles of these microRNAs in ankylosing spondylitis have not be addressed. We hypothesized that ankylosing spondylitis may have distingushed miRNA profiles compared with rheumatoid arthritis, which may play a critical role in pathogenesis and clinical manifestation. Objectives: To compare microRNA in synovial fluid of ankylosing spondylitis with of rheumatoid arthritis. To identify microRNA associated with bone homeostasis in ankylosing spondylitis. Methods: We determined the levels of 780 miRNAs of synovial fluid macrophages in 9 ankylosing spondylitis and 8 rheumatoid arthritis using TaqMan miRNA microarrays. Multiple test was done with Benjamini-Hochberg correction and miRNAs more than 1.5 fold change were selected. Results: One hundreds fourty three probes were selected after multiple test: 61 miRNAs were down-regulated and 82 miRNAs were up-regulated in AS. Among them, eight miRNAs associated with osteoclast or osteoblast were revealed: miR-129-5p and miR-1233 were down-regulated and miR-330-5p, miR-1226, miR-610, miR-1179, miR-335, and miR-625 were up- regulated in synovial fluid of ankylosing spondylitis. Conclusions: MicroRNA levels are distinctly increased or decreased in synovial fluid of ankylosing spondylitis compare with rheumatoid arthritis. Further validation studies with larger scale are warranted to fully explore the role of circulating microRNAs in ankylosing spondylitis. Disclosure of Interest: None Declared